1992
DOI: 10.3109/07357909209032783
|View full text |Cite
|
Sign up to set email alerts
|

Hexamethylmelamine and Low or Moderate Dose Cisplatin With or Without Pyridoxine for Treatment of Advanced Ovarian Carcinoma: A Study of the Eastern Cooperative Oncology Group

Abstract: A total of 248 analyzable patients with Stages III-IV ovarian epithelial cancer (114 with and 134 without prior chemotherapy) were randomized to one of four cisplatin (DDP)-hexamethylmelamine (HMM) regimens. In each, HMM, 200 mg/m2 was given orally daily on days 8-21 of each 21-day cycle. DDP was given i.v. on Day 1 at a dose of 37.5 mg/m2 (regimens A and B) or 75 mg/m2 (regimens C and D). In addition, since pyridoxine administration has been reported to reduce the neurotoxicity of HMM, that agent was given at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 14 publications
0
30
0
Order By: Relevance
“…The dose for this trial is also lower than the vitamin B6 administered in the Wiernik, et al [78] trial, which was 300 mg of vitamin B6 per day for 21 days after chemotherapy treatment. Although no toxicity from vitamin B6 was noted in Wiernik's trial, and CIPN was reduced, the dose of vitamin B6 was found to adversely affect response duration [78].…”
Section: -66mentioning
confidence: 99%
See 4 more Smart Citations
“…The dose for this trial is also lower than the vitamin B6 administered in the Wiernik, et al [78] trial, which was 300 mg of vitamin B6 per day for 21 days after chemotherapy treatment. Although no toxicity from vitamin B6 was noted in Wiernik's trial, and CIPN was reduced, the dose of vitamin B6 was found to adversely affect response duration [78].…”
Section: -66mentioning
confidence: 99%
“…Vitamin B6 was found to reduce CIPN [dose 100 mg of vitamin B6, pyridoxine hydrochloride, three times daily from days 1-21 of chemotherapy administration; equivalent to 300 mg/day]. However, it was also found to adversely affect response duration [78]. In 2010, Garg and Ackland found that vitamin B6 in cell culture examination was found to decrease CIPN associated with oxaliplatin administration, in the FOLFOX combination, without interfering with the anti-tumour activity [27].…”
Section: Role Of Pyridoxine In the Peripheral Nervous Systemmentioning
confidence: 99%
See 3 more Smart Citations